2019
DOI: 10.1186/s41241-019-0082-3
|View full text |Cite
|
Sign up to set email alerts
|

Subgingival microbial profile of women with breast cancer: a cross-sectional study

Abstract: Background: Some prospective studies have observed associations between periodontal disease and breast cancer. Therefore, the aim of the present study was to investigate the composition of the subgingival biofilm of women diagnosed with breast cancer, who also presented with chronic periodontitis. Methods: All subjects underwent clinical and microbiological assessment. Subgingival biofilm samples were taken from at least three sites of 44 women who had breast cancer. The mean levels and proportions of 40 bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 34 publications
(59 reference statements)
0
14
0
Order By: Relevance
“…Regarding a possible association between periodontitis and breast cancer, published studies have reported inconsistent findings, with some supporting a significant association while others claiming none. For example, a study done by Bernhard et al, (2019) to analyze the levels and proportions of 40 bacterial species in 144 sub-gingival plaque samples found an abundance of gram-negative species in the experimental group with the highest mean counts of two species viz. P. gingivalis and T. forsythia and high levels of other infectious periodontal pathogens, especially Fusobacterium and Prevotella sp.…”
Section: The Link Between Periodontitis and Breast Cancermentioning
confidence: 99%
“…Regarding a possible association between periodontitis and breast cancer, published studies have reported inconsistent findings, with some supporting a significant association while others claiming none. For example, a study done by Bernhard et al, (2019) to analyze the levels and proportions of 40 bacterial species in 144 sub-gingival plaque samples found an abundance of gram-negative species in the experimental group with the highest mean counts of two species viz. P. gingivalis and T. forsythia and high levels of other infectious periodontal pathogens, especially Fusobacterium and Prevotella sp.…”
Section: The Link Between Periodontitis and Breast Cancermentioning
confidence: 99%
“…With respect to the evaluation of specified follow-up durational data from the included articles, it was apparent that 2 studies [ 38 , 39 ], which stated their patient follow-up durations as being for over a period of less than 10 years, concurred to the significant impact that FN species within oral biofilm has on the promotion of female-specific BC pathogenesis (RR = 1.18, 95% CI = 1.15–1.29) ( Table 2 ). Comparatively, 2 of the included studies [ 41 , 43 ], both of which stated their patient follow-up periods as being more than 10 years, implied that the influence of FN species microbial levels within oral biofilms statistically possessed an insignificant effect on female-specific BC pathogenesis (RR = 1.41, 95% CI = 0.88–1.87) ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Results acquired “in vivo” from experimentations implemented on murine models revealed that FN-induced BC tumoral growths and their metastatic advancements were Fap2-dependant and reversible with antibiotics [ 18 ]. A further study in 2019 involved the evaluation of the microbial abundances of over 40 bacterial species within 144 subgingival plaque samples [ 38 ]. One of the highest mean counts of infectious pathogens obtained from the samples included that of the FN species, thus drawing a strong association between oral FN species-induced chronic inflammation as one of the risk factors for female BC [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 shows the commensals found in the oral cavity that are frequently related (directly or indirectly) to a variety of cancers in distant organs [ 31 , 33 , 47 , 49 , 50 ].…”
Section: Oral Microbiomementioning
confidence: 99%